2020
DOI: 10.21203/rs.3.rs-17019/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial trisomy 4q and monosomy 5p inherited from a maternal translocationt(4;5)(q33;p15) in three adverse pregnancies

Abstract: Abstract Background Carriers of balanced reciprocal chromosomal translocations are at known reproductive risk for offspring with unbalanced genotypes and resultantly abnormal phenotypes. After fertilization of a balanced translocation carrier with a normal gamete, the partial monomer or partial trisomy embryo will undergo abortion, fetal arrest or fetal malformatio. We reported a woman with balanced translocation who had two adverse pregnancies. Prenatal diagnosis was m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…30 A case study showed a copy gain of the distal region of chromosome 4 at segment 4q32.3q35.2 in a pregnant patient that presented with fetal edema and subsequent fetal loss. 31 Furthermore, the duplication of 16p13.11 is implicated in multiple congenital anomalies in pediatric patients (n=1645). 32 Mutations in MYH11 (myosin heavy chain 11) gene, among several genes in the 16p13.11 region, cause thoracic aortic aneurysms and/or dissections.…”
Section: Discussionmentioning
confidence: 99%
“…30 A case study showed a copy gain of the distal region of chromosome 4 at segment 4q32.3q35.2 in a pregnant patient that presented with fetal edema and subsequent fetal loss. 31 Furthermore, the duplication of 16p13.11 is implicated in multiple congenital anomalies in pediatric patients (n=1645). 32 Mutations in MYH11 (myosin heavy chain 11) gene, among several genes in the 16p13.11 region, cause thoracic aortic aneurysms and/or dissections.…”
Section: Discussionmentioning
confidence: 99%
“…30 A case study showed a copy gain of the distal region of chromosome 4 at segment 4q32.3q35.2 in a pregnant patient that presented with fetal edema and subsequent fetal loss. 31 Furthermore, the duplication of 16p13.11 is implicated in multiple congenital anomalies in paediatric patients (n = 1645). 32 Mutations in MYH11 (myosin heavy chain 11) gene, among several genes in the 16p13.11 region, cause thoracic aortic aneurysms and/ or dissections.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic placental lesions are found in DiGeorge sequence, characterised by hypoplasia in the umbilical cord arteries and widespread calcification of microthrombi in the arteries of the second and third order villous branches 30 . A case study showed a copy gain of the distal region of chromosome 4 at segment 4q32.3q35.2 in a pregnant patient that presented with fetal edema and subsequent fetal loss 31 . Furthermore, the duplication of 16p13.11 is implicated in multiple congenital anomalies in paediatric patients ( n = 1645) 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, ultrasound was used to break genomic DNA into 250–300 bp fragments. DNA libraries were constructed by end filling, adapter ligation, and polymerase chain reaction amplification 9 . Then, the DNA libraries underwent hybridization capture and were enriched by the xGen Exome Research Panel v2.0 (IDT).…”
Section: Methodsmentioning
confidence: 99%
“…DNA libraries were constructed by end filling, adapter ligation, and polymerase chain reaction amplification. 9 Then, the DNA libraries underwent hybridization capture and were enriched by the xGen Exome Research Panel v2.0 (IDT). High throughput sequencing was performed on the DNBSEQ-T7 platform (Beijing Genomics Institute).…”
Section: Wesmentioning
confidence: 99%